Memória institucional e sua possibilidade educativa : análise da revista O Sucesso do Grupo Claudino - Fortaleza, Keynayanna Késsia Costa (2018)
In recent years, we have seen the development and expansion of two areas of knowledge. Each one, in its own way, gains space in Brazilian organizations: Institutional Memory and Education. Institutional Memory, since the 1980s, has been firmly established in corporate environments, through the consolidation of projects and memorial products. Education, through the use of communication as an educational process, seeks to develop new forms of expression and diffusion of knowledge, providing new roles for the media. Our research was carried out together with a business conglomerate that emerged, in the 1950s, in the Northeast region of Brazil: the Claudino Group. Headquartered in Teresina, capital of the state of Piauí, the organization began investing in memory products with the production of its first institutional media, O Sucesso magazine, launched in 1972. The main objective of our research is to interpret the role of O magazine Success in the construction of the memory of the Claudino Group, as well as its educational bias, starting from the relationship established between the following themes: Institutional Memory, Media and Education. The research has a bibliographical and documentary character, with quantitative-qualitative approach, using Thompson's Depth Hermeneutics (2009), and the Content Analysis technique proposed by Bardin (1977). We intend, with our scientific research, to contribute to the debate about the performance of institutional media in Brazilian business environments, providing new perspectives and possibilities for Memory in Organizations.